A translational strategy employing physiologically based modelling to predict the pharmacological active dose of RO7119929, an oral prodrug of a targeted cancer immunotherapy TLR7 agonist. (3rd August 2022) - Rynn, Caroline; Umehara, Kenichi; Jiang, Tianyi; Ait-Goughoulte, Malika; Parrott, Neil
Abstract: RO7119929 is being developed as an orally administered prodrug of the TLR7-specific agonist and active drug, RO7117418, for the treatment of patients with solid tumours. In this publication, we present a case study wherein the human pharmacokinetics and pharmacological active dose were prospectively predicted following oral administration of the prodrug. A simple translational pharmacokinetic-pharmacodynamic strategy was applied to predict the pharmacological active dose of the prodrug in human. In vivo studies in monkey showed that an unbound plasma exposure of active drug of 1.5 ng/mL elicited secretion of key serum pharmacodynamic cytokine and chemokine biomarkers in monkey. This threshold of 1.5 ng/mL was close to the minimum effective concentration of active drug required to induce cytokine secretion in human peripheral blood mononuclear cells (3 ng/mL). Measured in vitro physicochemical and biochemical properties of the prodrug and active drug were applied as input parameters in physiologically based pharmacokinetic models to predict the pharmacokinetics of active drug after oral dosing of the prodrug in humans. Then, using the PBPK model, a dose which delivered an unbound plasma Cmax in line with the target pharmacodynamic threshold of 1.5 ng/mL was found. This defined the lowest pharmacologically active dose as 3 mg. The prodrug entered the clinic in 2020 in patients with primary or secondary liver cancers. Clear pharmacodynamic, transient, and dose-dependent cytokine induction was observed at prodrug doses > 1 mg.